Solar Powered Robot with Solar Tracker - Che Rozi, Muhaimin; JAFFERI, NOORMAZIAH (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This research project focuses on assessing the impact of dual-axis solar tracking on battery capacity in three different positions of solar panel. Using a dual-axis solar tracker, the study examined variations in energy generation by solar panels and subsequent power storage in batteries. The experiment showed the efficiency of harvesting solar energy for 15 days with three different panel positions during an average of five hours of sunlight exposure only able to generate 1.55Watts which is 62% of the actual specification of the solar panel. Maximum power output of the solar panel is 2.5W. Exposure for 16 hours with total of 1.55W only of power stored shows mthat there is likely to be a slightly error during the experiment. The second phase of the project is an application using stored energy to power a Bluetooth car. The measurement of battery capacity before and after the movement of the car in a distance of 6 meters with a motor gear power of 250W and the weight of the existing prototype which is 0.5415kg shows that the battery is depleted by 0.5 Ah per hour with an increase in load of 0.1 kg. The average power consumption for the weight of the car with a distance of 6 meters is 0.333 Ah. The study of the effect of load on battery performance provides nuanced insights into the complex relationship between load and electricity consumption in solar-powered systems. The outcomes of this research contribute valuable insights for the advancement of solar energy applications in various settings, providing a foundation for future innovations in sustainable energy solutions.